ARSENIC-BEARING ACCESSORY MINERALS IN SPHEROIDAL RHYOLITE AS RELATED TO ITS ORE POTENTIAL - Gundobin G.M.; Paradina L.F. (My University, 1988)
In the Paren' volcanic field in the Evensk sector of the Okhotsk-Chukotka belt, lavas form small extrusions that complete the evolution of a volcanoplutonic rock group of common origin, the derivative of latite-andesite magma. Their spheroids, which have a concentrically rhythmic texture, were studied with the Superprobe-733 microprobe. The results show that the alternating rhythms consist chiefly of quartz and either albite or potassic feldspar with as much as 10 percent albite. The accessory minerals in the spheroids are monazite, apatite and tourmaline. Profound differentiation of latite-andesite magma chambers could produce ultrasilicic magmas where low-temperature ore-bearing fluid or melt might be generated as an immiscible liquid. This possibility is consistent with features, including the enrichment of accessory minerals in arsenic, which plays a major role in the hydrothermal process, particularly in the transport of gold.